Postoperative new-onset atrial fibrillation causing acute embolic occlusion of the superior mesenteric artery: A case report - Cho, Jinbeom (Medicine (Baltimore), 2021)
RATIONALE: Postoperative atrial fibrillation following noncardiac surgery increases mortality, length of hospital stay, and medical expenses; moreover, compared to nonvalvular atrial fibrillation, it poses a similar risk of thromboembolic complications. In this report, we discuss our decision-making process for diagnosis and treatment in case with unexpected postoperative new-onset atrial fibrillation causing acute mesenteric ischemia. PATIENT CONCERNS: A 78-year-old male patient received varicose vein stripping and ligation in his right leg. The patient was previously healthy with no known comorbidities. The next day after surgery, he complained of sudden epigastric pain unresponsive to conservative treatment, and new-onset atrial fibrillation was observed on electrocardiography. DIAGNOSES: An abdominal computed tomography scan revealed acute embolic occlusion of the superior mesenteric artery INTERVENTIONS: Emergent surgical embolectomy was performed successfully. The time to operation from the recognition of abdominal pain was 6 h. Surgical critical care was performed for life-threatening ischemic reperfusion injury. OUTCOMES: The patient was discharged from the hospital on the 40(th) postoperative day. LESSONS: Atypical postoperative abdominal pain unresponsive to conservative treatment should be considered a surgical emergency, and a high level of clinical suspicion for acute mesenteric ischemia is required. Preoperative electrocardiography and postoperative telemetry might be helpful in some asymptomatic patients.